SNHG17 Serves as an Oncogenic lncRNA by Regulating the miR-361-3p/STC2 Axis in Rectal Cancer - Huang, Fuda; Li, Hua; Qin, Zebang; Wang, Anmin; Zhang, Ya; Guo, Junyu; Wei, Mingwei; Guo, Houji; Pu, Jian (Frontiers in Genetics, 2021)
Long noncoding RNA (lncRNA) have been reported to be crucial regulators for carcinogenesis, including rectal cancer. This work aimed to explore the roles and associated mechanisms of small nucleolar RNA host gene 17 (SNHG17) in rectal cancer. A quantitative real-time polymerase chain reaction was performed to measure the expression level of SNHG17 in rectal cancer tissues and cells. Cell counting kit-8 (CCK-8) assay and flow cytometry assay were conducted to measure the biological roles of SNHG17 in rectal cancer. In addition, luciferase activity reporter assay, RNA immunoprecipitation (RIP) assay, and rescue experiments were conducted to explore the mechanisms of SNHG17 in rectal cancer. The upregulation status of SNHG17 was identified in rectal cancer tissues and cells. Functionally, knockdown the expression of SNHG17 inhibits rectal cancer cell proliferation via stimulating cell apoptosis. In vivo assay showed that the knockdown of SNHG17 inhibits tumor growth. Furthermore, we showed that microRNA-361-3p (miR-361-3p) has decreased expression in tumor tissues and cells, and SNHG17 functions as a sponge for miR-361-3p. The upregulation status of stanniocalcin 2 (STC2) was also found in rectal cancer, and the knockdown of STC2 hinders cancer progression. In conclusion, lncRNA SNHG17 functions as an oncogenic lncRNA in rectal cancer by regulating the miR-361-3p/STC2 axis.